Implementation of PLC Outseal in the Control and Monitoring System for Chicken Farming Using SCADA Haiwell - Teguh Wahyudi; Zainal Abidin; Affan Bachri (G-Tech: Jurnal Teknologi Terapan, 2025)
The rapid growth of the poultry industry necessitates efficient environmental control in chicken farming. One of the main challenges is the high concentration of ammonia gas (NH₃) from chicken manure, which can adversely affect chicken health and productivity. This study presents the design and implementation of an automated control and monitoring system for chicken farms using a Programmable Logic Controller (PLC) Outseal and a Supervisory Control and Data Acquisition (SCADA) Haiwell. The system aims to maintain optimal environmental conditions, particularly ammonia gas concentration and temperature, which are critical for poultry health and productivity. The system utilizes MQ-135 and LM35 sensors to monitor ammonia and temperature levels, respectively, and is built on a master-slave architecture using the MODBUS RTU protocol. Data is transmitted in real-time to the SCADA dashboard, enabling automated control of the blower system. Experimental results demonstrated that the system effectively maintained ammonia levels between 20–35 ppm and temperature between 35–38°C. The LM35 sensor achieved an average error rate of 0.83%, while the MQ-135 sensor showed an error of 1.80%. The RS-485 communication protocol enabled stable data transfer up to 200 centimeters. These results indicate that the system can significantly improve poultry farming management through automation and environmental optimization.